IMPROVING THE QUALITY OF ISLAMIC EDUCATION THROUGH THE ROLE OF STUDENTS - Prasetyo, Teguh (Universitas Djuanda Bogor, 2016)
Education is a conscious effort made by individuals and institutions through teaching,coaching, and training for developing human potential in the face of challenges in the future.Students as agents of change to take an important role in society. One of the implementationof the active role of students and professors University Djuanda Bogor implement KuliahKerja Nyata (KKN) started in August 2016 for an independent and integrated with thefindings in the field. The location is in the implementation of Village Buntar, South Bogor. Theresult of this dedication also involve faculty and students. One of the changes is the concernof the people of Village Buntar to improve the quality of education, especially through Islamicelementary schools and early childhood. The efforts or programs that have beenimplemented include; (1) teaching in educational institutions madrasah and early childhood,(2) Tutoring, (3) training of learning tools, (syllabus and lesson plans), (4) Socialisation ofmadrasah islamic education, and (5) seminar to be a professional teacher. Recommendationsby the dedication of the students can give recommendations to citizens, teenagers, structuralvillages, and the city government can work synergistically to promote education in VillageBuntar.